Land poverty and emerging ruralities in Cambodia: Insights from Kampot province (2014)
Rural change in Cambodia manifests itself in rapidly declining land availability for the smallholder sector, posing the question of how farmers may be able to deal with limited access to land. In this paper, we discuss with a case study village and household livelihood strategies of smallholders currently operating under land-constrained conditions. Based on an integrated assessment of a smallholder village in Kampot province, we illustrate in quantitative terms how land shortage is creating problems of surplus generation and liquidity issues in monetary and non-monetary flows. At the household level, livelihood diversification based on the involvement of productive resources other than land may play an increasing role, particularly in the future, when levels of land shortage may increase. At the village level, smallholder may respond through institutional innovation, in particular through the establishment of a community banking system and a paddy rice bank to provide money and rice credits to overcome transitory shortages and to cover investment costs for additional productive resources. Thus, in this case, we observe the emergence of new patterns of livelihood in rural areas, based on the integration of non-land-based economic activities and new institutional settings.